Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Membrane vesicle secretion and prophage induction in multidrug‐resistant Stenotrophomonas maltophilia in response to ciprofloxacin stress - Simon Devos; Wouter Van Putte; Jolien Vitse; Gonzalez Van Driessche; Stephan Stremersch; Wim Van Den Broek; Koen Raemdonck; Kevin Braeckmans; Henning Stahlberg; Misha Kudryashev; Savvas N. Savvides; Bart Devreese (Environmental Microbiology, 2017)
Summary Several bacterial species produce membrane vesicles (MVs) in response to antibiotic stress. However, the biogenesis and role of MVs in bacterial antibiotic resistance mechanisms have remained unclear. Here, we studied the effect of the fluoroquinolone ciprofloxacin on MV secretion by Stenotrophomonas maltophilia using a combination of electron microscopy and proteomic approaches. We found that in addition to the classical outer membrane vesicles (OMV), ciprofloxacin‐stimulated cultures produced larger vesicles containing both outer and inner membranes termed outer‐inner membrane vesicles (OIMV), and that such MVs are enriched with cytosolic proteins. Remarkably, OIMV were found to be decorated with filamentous structures identified as fimbriae. In addition, ciprofloxacin stress leads to the release of bacteriophages and phage tail‐like particles. Prophage induction by ciprofloxacin has been linked to pathogenesis and horizontal gene transfer in several bacterial species. Together, our findings show that ciprofloxacin treatment of S. maltophilia leads to the secretion of a heterogeneous pool of MVs and the induction of prophages that are potentially involved in adverse side‐effects during antibiotic treatment.

EFSA Guidelines on the environmental risk assessment of genetically modified animals in the EU: the process and risk assessment considerations - Sylvie Mestdagh; Yann Devos; Christina Ehlert; Yi Liu; Nancy Podevin; Stefano Rodighiero; Elisabeth Waigmann; József Kiss; Joe N. Perry; Jeremy B. Sweet (Journal of Consumer Protection and Food Safety, 2014)

EFSA’s scientific activities and achievements on the risk assessment of genetically modified organisms (GMOs) during its first decade of existence: looking back and ahead - Yann Devos; Jaime Aguilera; Zoltán Diveki; Ana Gomes; Yi Liu; Claudia Paoletti; Patrick du Jardin; Lieve Herman; Joe N. Perry; Elisabeth Waigmann (Transgenic Research, 2014)

Resistance evolution to the first generation of genetically modified Diabrotica-active Bt-maize events by western corn rootworm: management and monitoring considerations - Yann Devos; Lisa N. Meihls; József Kiss; Bruce E. Hibbard (Transgenic Research, 2013)

Impact of combination therapy with aminoglycosides on the outcome of ICU-acquired bacteraemias - P.-Y. Delannoy; N. Boussekey; P. Devos; S. Alfandari; C. Turbelin; A. Chiche; A. Meybeck; H. Georges; O. Leroy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Feral genetically modified herbicide tolerant oilseed rape from seed import spills: are concerns scientifically justified? - Yann Devos; Rosemary S. Hails; Antoine Messéan; Joe N. Perry; Geoffrey R. Squire (Transgenic Research, 2012)

Adult community-acquired bacterial meningitis requiring ICU admission: epidemiological data, prognosis factors and adherence to IDSA guidelines - H. Georges; A. Chiche; S. Alfandari; P. Devos; N. Boussekey; O. Leroy (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Comparative Sequence Analysis of the Phytochrome C Gene and its Upstream Region in Allohexaploid Wheat Reveals New Data on the Evolution of its Three Constituent Genomes - Katrien M. Devos; James Beales; Yasunari Ogihara; Andrew N. Doust (Plant Molecular Biology, 2005)

Patterns of chloroplast diversity among western European Dactylorhiza species (Orchidaceae) - N. Devos; D. Tyteca; O. Rasp; R. A. Wesselingh; A.-L. Jacquemart (Plant Systematics and Evolution, 2003)